Challenges in building domain ontology for minority languages - Talita, Panceras; Yeo, Alvin Wee; Kulathuramaiyer, Narayanan (Computer Applications and Industrial Electronics, 2010)
The development of domain ontology is important in building a list of vocabulary whereas the process of sharing and reusing this knowledge management can be accomplished easily. This paper presents the challenges that arise in the ontology development area by focusing on one domain concept. Domain concept here can be transversed from different disciplines, such as agricultural, medicine, human-anatomy, and automotive. The assessments on the challenges vary among numerous ontology projects. The challenges can be influenced by the use of minority languages as the local resources since these languages are resource constrained compared to languages such as English that are rich in resource availability. Apart from that, minority languages tend to have issues concerning different morphological structures and grammatical structures. Numbers of existing ontologies for different disciplines had been produced in English language but little has been done for indigenous languages such as Iban. The main contribution here resides in the ontology development itself, which emphasise on the best means for a beginner to design, develop and deploy the ontology. Research based on the previous work and possible solution is presented in this paper.